A classical control approach to the power management of an all-electric hybrid vehicle. - Marco, James; Vaughan, Nicholas D. (Cranfield University, 2009)
Modern hybrid electric vehicles (HEVs) often employ all-electric powertrains that utilise hybrid sources of power and energy; such as batteries, fuel cells and ultracapacitors. This paper describes the design, simulation and experimental verification of a power management control system that manages a high voltage battery, a DC-DC boost converter and an ultracapacitor within a front-wheel drive HEV in which the motive power for the vehicle comes from two electrical machines. As part of this study, consideration is given to the complete control system design life-cycle including plant model development, algorithm design and software implementation on the target electronic control unit (ECU). Off-line simulation and initial experimental results are presented showing the vehicle operating on a powertrain dynamometer as one means of demonstrating the ability of the ultracapacitor to limit the transient demands placed on the battery during periods of vehicle acceleration and regenerative braking.
Keywords: Hybrid electric vehicle (HEV); systems modelling and control; power electronics; ultracapacitor